2011
DOI: 10.1007/s10549-011-1417-2
|View full text |Cite
|
Sign up to set email alerts
|

Complete response in HER2+ leptomeningeal carcinomatosis from breast cancer with intrathecal trastuzumab

Abstract: Trastuzumab, a monoclonal antibody against the HER2 receptor, is a major breakthrough in the treatment of HER2+ breast cancer. However, its high molecular weight precludes it from crossing the intact blood-brain barrier, making the central nervous system a sanctuary to HER2+ breast cancer metastases. We prospectively assessed functional outcome and toxicity of administering trastuzumab directly into the cerebrospinal fluid of a patient with leptomeningeal carcinomatosis and brain metastases from HER2+ breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…[53] Additionally, trastuzumab and topotecan has recently been used in intrathecal chemotherapy in MC from breast cancer. [54][55][56] Topotecan, an alkylating agent, showed variable effects. [57] A retrospective review of 149 patients with breast cancer-related MC showed that there was no significant difference in overall survival between patients treated with intra-CSF liposomal cytarabine and methotrexate, with the median overall survival of 4.2 months.…”
Section: Intrathecal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…[53] Additionally, trastuzumab and topotecan has recently been used in intrathecal chemotherapy in MC from breast cancer. [54][55][56] Topotecan, an alkylating agent, showed variable effects. [57] A retrospective review of 149 patients with breast cancer-related MC showed that there was no significant difference in overall survival between patients treated with intra-CSF liposomal cytarabine and methotrexate, with the median overall survival of 4.2 months.…”
Section: Intrathecal Therapymentioning
confidence: 99%
“…[81,82] A patient with MC received 67 cycles of weekly 25 mg IT trastuzumab with a long survival time (27 months) after MC diagnosis and dramatic clinical improvement. [54] Moreover, intra-CSF trastuzumab combined with intra-CSF MTX and ara-C has been performed in two patients with MC. The survival time of the two patients was 13.5 months and 6 months respectively with a clinical benefit and without substantial toxicity.…”
Section: Intrathecal Therapymentioning
confidence: 99%
“…A HER-2-pozitív emlődaganatos betegeknél a zsigeri metasztázisok kezelésében alkalmazott trastuzumab, pertuzumab és TDM-1 is képes az agyi áttétek progresszióját lassítani, illetve a teljes túlélést növelni [8][9][10], bár ebben az indikációban alkalmazásukra egyértelmű ajánlás még nem született. Meningitis carcinomatosa esetén intrathecalis trastuzumabkezelés mellett elért komplett klinikai remisszióról is szól esettanulmány [11].…”
Section: Táblázatunclassified
“…However, trastuzumab has also been demonstrated to be effective when used as single agent in the treatment of metastatic ErbB2-positive breast cancer (29). Although trastuzumab does not cross the blood-brain barrier due to its large molecule size, its administration via the intrathecal route has been reported to be effective for brain metastasis of ErbB2 positive breast cancer (24). In recent years, research efforts have focused on improving the delivery of trastuzumab to the Our study results were consistent with all of these studies and indicated nuclear accumulation of β-catenin in all of the ACP tissue specimens, predominantly accumulated in epithelial cells within the whorl-like arrays (7,8).…”
Section: Zuhur Ss Et Al: Immunohistochemical Expression Of Erbb2 In mentioning
confidence: 99%